Synthesis and Biological Evaluation of Termini-Modified and Cyclic Variants of the Connexin43 Inhibitor Peptide5 - Crystal Chan, Sin Hang; Griffin, Jarred M.; Clemett, Connor A.; Brimble, Margaret A.; O’Carroll, Simon J.; Harris, Paul W. R. (Frontiers in Chemistry, 2022)
Peptide5 regulates both cellular communication with the cytoplasm (hemichannels) and cell to cell communication (gap junctions) and both processes are implicated in neurological pathologies. To address the poor in vivo stability of native Peptide5 and to improve its activity, twenty-five novel Peptide5 mimetics were designed and synthesized. All analogues underwent biological evaluation as a hemichannel blocker and as a gap junction disruptor and several were assessed for stability in human serum. From this study it was established that acylation on the N-terminus was tolerated in the hemi-channel assay and replacing a Lys with its D-variant both good hemichannel and gap junction activity Cyclic peptide variants generally were not tolerated in either assay although they possessed more stability in human serum.